(untitled) (Archive of Conferences, 2021)
Antonin Dvoják, together with Bedrjix Smetana, is a brilliant representative of the Czech school of composition. His work is notable for a variety of genres - symphonies (the most famous - in the minor "New World" op.95, 1893), string quartet, operas (the most famous - "Mermaid"), symphonic poems, songs, mass, piano works and instrumental concerts. Brahms once wrote of the cello concerto of the most famous author among music lovers, the minor op.103: "If I had known that a cello could do such a thing, I would have written it myself."